Educational Efficiency and the Most Common Disturbing Factors in the Teaching of Physical and Health Education in Higher Primary School Classes - Milenović, Hadži Živorad M.; Vidaković, Hadži Miloš V.; Petrović, Jelena S. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
The goal of learning in physical and health education (PHE) is for the student to improve physical abilities, motor skills and knowledge in physical and health culture, in order to preserve health and apply proper and regular physical exercise in modern living conditions and work. On the basis of the goal of the PHE teaching, the biological, pedagogical, and educational tasks are determined, the realization of which leads to the outcome of the PHE teaching.The biological tasks of physical education imply that a positive influence on students’ proper growth and development is possible if the teacher is familiar with the structure and functions of the most important organic systems, the biological laws of development, and the impact of physical exercises on the organism. Pedagogical tasks include educational and learning tasks that intertwine and complement each other. Learning tasks should primarily contribute to the acquisition of motor skills and habits (sports-technical education), but also to the theoretical knowledge aiming to understanding the purpose of exercise, structure, method, and performance of certain exercises. Educational tasks, the teaching content, methods and forms of teaching are planned in accordance with their educational potential so that during the PHE classes, the students acquire the qualities and values contained in the PHE syllabus and at the same time represent universal human qualities and values that contribute to the development of the student’s complete personality which is the ultimate ideal to strive for in education. By achieving the goals of the PHE syllabus, students acquire knowledge, skills, attitudes, and values about exercise (basic terms about exercise, how to perform an exercise and what a specific exercise is for), physical education, sports, recreation, and health. Specially planned and designed information about exercise and health is delivered immediately before, during, and after exercise in class. The goal, tasks, and outcomes of the course are achieved through the teaching of physical and health education (2 school hours per week) and compulsory physical activities for each student (1.5 school hours per week).This research is focused on the most frequent disruptive factors that lower the efficacy of implementation of PHE teaching in the higher grades of elementary school. The research was based on the general assumption that the teaching of physical and health education significantly contributes to the growth, development, health, upbringing, and education of students, but that it is not implemented as effectively as it could be. In contrast to many previous studies in which answers were collected from teachers or parents, in this research the answers were collected from the students in the higher grades of primary school themselves, since they are direct participants in the PHE classes and their development, education, and learning in PHE classes is the main outcome of teaching (Parkes et al, 2022; Amamou et al, 2021; Holden et al, 2020). It was interesting to analyse from the students’ point of view what the most frequent disturbing factors are and whether some of the criterion variables affect it, such as the class the students attend; grade in physical education in the previous semester; and the general success of students in the previous semester. The research was conducted in January 2023 on a sample of 101 students at the Kirilo Savić Elementary School in Ivanjica. The data collected by the Scale – EE-MCDF-RPHET (α = 0,602) were processed by factor analysis, analysis of variance, and the Mann-Whitney U test.Factor analysis identified five factors that indicate educational efficiency and the most disruptive factors of PHE teaching. They are: 1) inconsistent practicing of different sports contrary to the student's assessment of the educational efficiency of the PHE teaching; 2) effectiveness of teaching; 3) the importance of active sports training; 4) football training contrary to the student's assessment of the educational efficiency of the PHE teaching; and 5) student safety. The analysis of variance showed that such assessments of students are not significantly influenced by the class they attend, success in physical and health education and education and general success in the previous semester, while the Mann-Whitney U test determined that such assessments of students are significantly influenced by actively playing a sport.Based on the results of the research, a proposal was made for an innovative approach to the implementation of physical and health education teaching in elementary schools, according to innovative teaching systems and innovative didactic-methodical teaching models. Teaching according to these models is planned, implemented, and evaluated in a multi-step and reverse design. In such a class, students are more involved in practicing, active learning, and participating in PHE classes. Based on the desired outcomes of the PHE classes, the goal is for as many students as possible, preferably all, to get involved in the work of sport clubs and in the future take up sports. In this way, the knowledge, skills, habits, and abilities the students develop in PHE classes and in sports clubs will be of fundamental importance for students outside the classroom and serve them in their daily activities in various situations in the family, school, local environment and wider social community. In order to achieve this, it is necessary to constantly strengthen the competences of teachers for planning, implementation, and evaluation of PHE teaching.
Keywords: PHE; physical and health education; goals of teaching; tasks of teaching; utcomes of teaching; evaluation of teaching; most common advantages of teaching; possible shortcomings of teaching